High Crimes and Misunderstandings: Interpretation of the Impeachment Clause in the Twenty-First Century - Parillo, Jessica Lynne (Tufts Archival Research Center, 2022)
This paper contributes to an extensive body of literature on the impeachment clause by analyzing how the ambiguous phrase “high crimes and misdemeanors” is interpreted in the twenty-first century. The contemporary Congress is displaying unprecedented levels of hyperpolarization - why, then, were votes to convict in the double impeachments of President Trump (2020 and 2021) more bipartisan than in any prior presidential impeachment trial? To answer this question, traditional approaches to interpreting the impeachment clause, namely legal realism and legal formalism, are first discussed. I then conduct a historical analysis of the origins of the impeachment clause in English law, followed by a textual analysis of the 21 impeachment resolutions charged against civil officers. A comparison of the articles charged in judicial impeachments and presidential impeachments reveals substantial differences in application of the impeachment clause. Particularly, inappropriate conduct by a president must be significantly more offensive than a violation of the “good behavior” standard to warrant removal from office. Finally, statistical modeling is used to evaluate the statements made by the seven Republican senators who broke with party lines to convict President Trump in his 2021 impeachment trial. The data shows that criticism of the investigation conducted by the House, as well as characterizing the impeachment proceedings as overly partisan, are the strongest predictors of voting outcome in a Senate impeachment trial. Understanding how congressional interpretation of the impeachment clause has changed throughout history can shed light on whether impeachment remains an effective tool of executive accountability in the current political climate. I find that while there is a growing trend in the House of Representatives to use impeachment as a political threat, the partisan nature of impeachments does not render Article II Section IV completely ineffective.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Political Science.; Advisor: Jeffrey Berry.; Committee: Jeffrey Berry and Brian Schaffner.